PENINGKATAN KUALITAS KESEHATAN MASYARAKAT ERA PANDEMIC COVID-19 MELALUI PEMANFAATAN TANAMAN OBAT KELUARGA SEBAGAI SUMBER IMMUNOMODULATOR - Sunandar Ihsan; Yamin Yamin; Muhammad Handoyo Sahumena; Wa Ode Sitti Zubaydah; Arfan Arfan (Jurnal Pengabdian NUSANTARA, 2022)
Coronavirus Diseases 2019 (COVID-19) is a disease caused by a new coronavirus strain (SARS-CoV-2) which then mutates into various variants including the omicron variant, alpha variant, beta variant, and gamma variant. Where, transmission will pose a high risk when the body's immunity is low. The purpose of this activity is to provide information on various "Family Medicine Gardens" that can function as Immunomodulators to the general public, as well as students, both junior high school (SMP) and elementary school (SD) students. The implementation of this activity is carried out face-to-face and is packaged in the form of socializing the benefits of the Family Medicinal Garden (TOGA) as a source of immunomodulators, together with the community practicing making Family Medicinal Plant gardens in the Poasia and Kambuh Districts as well as the School Environment. In addition, this is also done by distributing leaflets containing information on the types of plants that act as immunomodulators and how to make them.